The impact of older employees’ generativity on job dedication: a socioemotional selectivity perspective - Gong, Zhenxing; He, Yongqi; Li, Miaomiao (Frontiers in Psychology, 2026)
IntroductionAs organizations worldwide grapple with an aging workforce and extended careers, understanding and enhancing the psychological mechanisms underpinning older employees’ job dedication has become increasingly crucial. Building upon Carstensen’s socioemotional selectivity theory, this study explores how older employees’ generativity translates into job dedication through organizational commitment, with trust serving as a key boundary condition.MethodsWe address this gap through a three-wave longitudinal study of 489 older employees across multiple organizations in eastern China. Using exploratory factor analysis, confirmatory factor analysis, correlation analysis, and Bootstrap mediation testing, we examine the proposed relationships.ResultsThe findings indicate that: (1) generativity exerts a significant positive effect on job dedication (β = 1.06, p < 0.01); (2) generativity promotes job dedication by influencing organizational commitment (β = 0.99, p < 0.01), which in turn enhances job dedication (β = 0.61, p < 0.01); (3) cognitive trust (β = 0.15, p < 0.01) and affective trust (β = 0.18, p < 0.01) significantly moderate the effect of generativity on organizational commitment.DiscussionTheoretically, our findings extend the socioemotional selectivity theory by demonstrating how generativity acts as a psychological bridge between older employees’ future time perspective and their job dedication. Practically, we identified specific trust-building practices that organizations can implement to unlock the generativity motivation potential of older employees. Thus, this study provides theoretical advances and actionable insights for developing age-inclusive workplaces.